ROLE OF MANAGEMENT ACCOUNTING IN DECISIONS ON MANAGEMENT ORGANIZATION - N. I. Khomutetskaya; A. G. Golub (Фармация и фармакология (Пятигорск), 2015)
The article is devoted to the introduction of management accounting in the work of organizations (enterprises) that will improve the efficiency of administrative decisions will contribute to the flexibility and adaptability of the organization to changes in the external environment, increased productivity and efficient use of all resources of the organization.